1970
DOI: 10.1203/00006450-197007000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Observations on So-called Hereditary Tyrosinemia

Abstract: ExtractDecreased activities of methionine-activating enzyme (ATP: L-methionine-S-adenosyl-transferase, EG. 2.5.1.6) (23 and 18 versus normal 86 nmoles product produced/mg soluble protein/h) and cystathionine synthetase [30] (28 and 6 versus normal of 98 nmoles product produced/mg soluble protein/h) in the presence of normal activity of cystathionase [30] (104 and 108 versus normal of 125 nmoles product produced/mg soluble protein/h) were demonstrated in the liver of two patients with so-called hereditary tyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

1972
1972
1991
1991

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(23 citation statements)
references
References 16 publications
1
20
0
2
Order By: Relevance
“…Since AFP production correlates with the degree of methionine metabolism block in these patients, these authors have suggested that the normal ontogenic repression of AFP might depend on a methionine-related metabolic event, for example, the activation of a differentiation control mechanism working through a transmethylase pathway. This suggestion is based in part upon an observation by Gaull et al (1970) that levels of methionine adenosyltransferase (MAT) are greatly decreased in hypermethionemic HT children. More recently Liau et al (1979) reported that livers of children who died of HT showed abnormal MAT isozyme patterns.…”
Section: -Mc Depletion During Tumour Development 467mentioning
confidence: 99%
“…Since AFP production correlates with the degree of methionine metabolism block in these patients, these authors have suggested that the normal ontogenic repression of AFP might depend on a methionine-related metabolic event, for example, the activation of a differentiation control mechanism working through a transmethylase pathway. This suggestion is based in part upon an observation by Gaull et al (1970) that levels of methionine adenosyltransferase (MAT) are greatly decreased in hypermethionemic HT children. More recently Liau et al (1979) reported that livers of children who died of HT showed abnormal MAT isozyme patterns.…”
Section: -Mc Depletion During Tumour Development 467mentioning
confidence: 99%
“…Valid comparison with mature human brain is not possible, of course, because biopsy controls cannot be obtained. However, in Table II there are given the activities of these enzymes as well as the concentrations of cystathionine in selected areas of the brain, obtained at autopsy, from a 6-month-old infant with so-called "hereditary tyrosinemia" [7]. It should also be noted that values for the "control" brain may represent a minimum estimate of the activities of methionine-activating enzyme and cystathionine synthase, since it was shown that these activities are considerably reduced in crude extracts of liver from patients with so-called "hereditary tyrosinemia."…”
Section: Enzymatic Assays and Cystathionine Concentration In Fetal Brainmentioning
confidence: 99%
“…6, 0.8) Gaul1 et al (8) found decreased activities of methionine ad- enosyltransferase and cystathionine P-synthase, as well as p- Vmax' Range (0.9,1.9) ... (12.0-16.3) (1.7, 1.9) HPPA oxidase, in the liver of tyrosinemia type I and concluded that these enzyme deficiencies were probably secondary mani-* Abbreviations: see "Abbreviations. "…”
Section: Methodsmentioning
confidence: 99%
“…The excessive excretion of phenolic acids has led some investigators (12,21) to suggest that the enzyme, p-HPPA oxidase, is involved in the pathogenesis of this disorder. In fact, several authors (15,23) confirmed that the p-HPPA oxidase activity was markedly reduced in the liver of patients; this was once considered to be a primary defect, but still is controversial (2,8).…”
mentioning
confidence: 98%